Enzyme-controlled hygroscopicity and proton dynamics in sea cucumber (Stichopus japonicus) ovum peptide powders. (October 2018) - Wang, Ke; Sun, Na; Li, Dongmei; Cheng, Sheng; Song, Liang; Lin, Songyi
Abstract: The enzyme-controlled hygroscopicity of peptide powders during storage at room temperature may have a profound effect on their properties. The present study aims to elucidate hygroscopicity, proton dynamics, as well as effect on the microstructure of sea cucumber ovum peptides (SCOPs) powder produced with different enzymes during storage. The SCOPs produced with Alcalase exhibited the strongest moisture absorption capacity, which was significantly higher than those of SCOPs produced with papain, neutrase, and trypsin ( P < .05). This might be attributed to the greater hydrolysis of Alcalase and producing more polar groups. Moreover, the proton dynamic and the transformations of water populations varied greatly among the SCOPs with different enzymes. Even so, the SCOPs exhibited a common water migration rule that free water was gradually transformed into immobilized water that was simultaneously converted into bound water after moisture absorption. The hygroscopicity induced morphological changes of SCOPs, which was converted from a smooth amorphous structure into different sizes of particle agglomerates. Moreover, the SCOPs produced with Alcalase displayed more and smaller agglomerates than those produced with papain, neutrase, and trypsin. This study provides a theoretical basis for quality assurance of peptide powders, particularly those produced with Alcalase. Graphical abstract: Highlights: The proton dynamics of four SCOPs was monitored by DVS and LF-NMR. The hygroscopicity of four SCOPs during storage was analyzed. The moisture absorption induced morphological changes of SCOPs. The SCOPs- alcalase has the strongest hygroscopicity among four samples.